Effectiveness of Long Term Supervised and Assisted Physiotherapy in Postsurgery Oral Submucous Fibrosis Patients - S. Kale; N. Srivastava; V. Bagga; A. Shetty (Case Reports in Dentistry)
Oral submucous fibrosis is one of the leading potentially malignant disorders prevailing in India. A number of conservative and surgical treatment options have been suggested for this potentially malignant disorder (Arakeri and Brennan, 2013). While the role of physiotherapy has been highlighted in the conservative management, its importance in postsurgical cases to avoid scar contracture and subsequent relapse has not been given due importance in the literature. The following is a case report of a male patient surgically treated for OSMF (oral submucous fibrosis) and meticulously followed up for recalls and physiotherapy. The constant supervision and motivation for physiotherapy along with the constant assistance helped achieve satisfying results.